2010
DOI: 10.1183/09059180.00004810
|View full text |Cite
|
Sign up to set email alerts
|

Association of pulmonary aspergilloma and allergic bronchopulmonary aspergillosis

Abstract: Finally, this case demonstrates the importance of timely and correct diagnosis in PAH. Evidence suggests that treatment of mildly symptomatic patients can be beneficial, and indeed data from the EARLY trial [5] led to regulatory authority approval for the use of bosentan in the treatment of PAH patients in NYHA/WHO FC II and a recommendation for treatment of such patients in recent guidelines [3]. In this case the patient's condition deteriorated between her initial misdiagnosis of post-partum depression and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Concurrent ABPA and aspergilloma is likely to increase the severity of the disease with more frequent exacerbations of asthma and possibly increased risk of haemoptysis [250]. Such patients should be monitored carefully and antifungal therapy or resection of the aspergilloma may be necessary in symptomatic patients [250,251].…”
Section: Pulmonary Aspergillus Overlap Syndromesmentioning
confidence: 99%
“…Concurrent ABPA and aspergilloma is likely to increase the severity of the disease with more frequent exacerbations of asthma and possibly increased risk of haemoptysis [250]. Such patients should be monitored carefully and antifungal therapy or resection of the aspergilloma may be necessary in symptomatic patients [250,251].…”
Section: Pulmonary Aspergillus Overlap Syndromesmentioning
confidence: 99%
“…Previous studies have reported the outcome of surgical resection for aspergilloma in ABPA patients, due to pneumothorax [ 8 ] and hemoptysis [ 9 , 10 ]. However, only one case involved a report of surgical resection for aspergilloma that contributed to disease control of ABPA; the patient was followed up without ABPA treatment for 6 months after receiving surgical resection for aspergilloma with antifungal therapy [ 11 ], whereas our case was followed up for a number of years.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in Aspergillus colonisation of the airways in ABPA has been noted with itraconazole. The patient reported in this issue of the European Respiratory Review responded well to wedge resection of the aspergilloma and itraconazole post-operatively [23]. A significant reduction in the total IgE level was noted at 5 months and itraconazole was discontinued after 1.5 yrs.…”
mentioning
confidence: 84%
“…In spite of similar immunopathological responses, concomitant occurrence of ABPA and AAS is infrequently reported [19][20][21][22]. In this issue of the European Respiratory Review, MONTANI et al [23] describe a 50-yr-old female with concomitant ABPA and aspergilloma. Even though chronic lung damage appears to provide a favourable milieu for aspergilloma formation, the concomitant occurrence of aspergillomas is rather uncommon in patients with ABPA, even in the presence of cavitation [24,25].…”
mentioning
confidence: 99%